Bagian yang Hilang dalam Pembicaraan Akademisi Indonesia tentang Sastra Siber - Dipa Nugraha; Suyitno Suyitno (Fakultas Bahasa dan Seni UNP, 2020)
There is a missing subject in the conversations on Indonesian cyberliterature. This case study research identifies academic conversations on cyberliterature in Indonesia. Literature review using articles written by Indonesian academia is used to build an assumption on the discursive development of cyberliterature in Indonesia which misses electronic literature. The assumption is then verified with the data collected from one-shot method survey. The survey using two simple questions targeted Indonesian lecturers from several universities in Java, Sumatera, and Kalimantan. Qualitative content analysis is used to describe our findings. The analysis reveals that Indonesian academia conversations on cyberliterature only focus on digital publishing and the freedom of expression offers by the presence of the internet. The conversations on cyberliterature by Indonesian academia have not really covered electronic literature and how it may develop in the Indonesian literary context.